(untitled) (Global Journal of Human-Social Science, 2015)
Since the adoption of the neoliberal policy in Nigeria in the 1980s, its impact on the human development indices of the citizenry has not been satisfactory as manifested by the unequal income distribution gap between the rich and the poor over the years. Besides, the health conditions of Nigerians have experienced a decline as revealed by the increasing rate of child/infant mortality and maternal mortality which expresses the failure of government reforms in adequately addressing some aspects of the United Nations Millennium Development Goals (MDGs). Using secondary sources of data, this paper investigated how government’s implementation of the neoliberal policies had impacted on the healthcare and human development indices of the citizens. It was observed that rather than improve the healthcare situation and human development indices of citizens, the Bretton Woods-authored reforms have rather narrowed opportunities for healthcare and human development in Nigeria. To improve the declining human development indices of citizens, the paper recommends the roll out of a politics of paradise to rein in the poverty and deprivation suffered by many Nigerians and the need for a human-faced approach to economic reforms, among others.